AN ANALYSIS OF SOUND DELETION IN SUMBAWA LANGUAGE - Ardian Sukma; Iwan Jazadi; Supriadin (GLOBAL: Education Language and Humanity Journal, 2023)
This study uses a qualitative descriptive method in analyzing the data. There were 10 participants with 15 conversations held in Telaga Bakti Hamlet. To collect data, three techniques were used, namely observation, audio recording, and introspection. In analyzing the data, the researcher used four steps, namely: (1) Identifying the data, (2) Classifying the data, (3) Describing the data, and (4) Explaining the data. Some research results are described in the form of words: Apheresis: 'tita' (while ago). From the word 'tita' which means (while earlier) one or more phonemes have been zeroed out at the beginning of the word. The whole word must be 'satita', the word 'satita' focuses on the first phoneme, namely the consonant phoneme 's' and the vowel 'a'. Syncope: 'malo?' (Is it true?). The elimination of sounds is caused by the language environment and as an effort to save speech by speakers. Based on the research results, the researchers concluded that the Sumbawa language produced was divided into three forms, namely apheresis, syncope, and apocope. Factors causing the loss of sound are efforts to save speech and as a common language in society.